Ageing successfully with haemophilia: A multidisciplinary programme. Issue 1 (6th August 2017) - Boccalandro, E.; Mancuso, M. E.; Riva, S.; Pisaniello, D. M.; Ronchetti, F.; Santagostino, E.; Peyvandi, F.; Solimeno, L. P.; Mannucci, P. M.; Pasta, G.
Abstract : Introduction: Persons with haemophilia (PWH) born before the middle 1970s have spent a substantial part of their lives without the benefits of replacement therapy, that became available on a relative large scale only during the 1970s. As a consequence, this group of PWH, although still relatively young, suffers from musculoskeletal and functional problems that are typical of old people. Methods: We report herewith the short‐term results of a project based upon a multidisciplinary training programme led by a physiotherapist and an occupational therapist, that was implemented over a period of 12 months in 40 patients with severe or moderate hemophilia A or B born before the middle 1970s and regularly followed‐up at a comprehensive haemophilia treatment centre in Italy. The project was aimed to provide information and skills in order to empower the older PWH carrying physical handicaps and functional limitations that had resulted from the inadequate management in their early ages, and to enable them to cope more efficiently with their crippling disease and prevent further disabilities. Results and Conclusions: The comparison of the data obtained before and after the 12‐month programme found marginal improvements, but the purpose of this programme was indeed to offer a blueprint for the future. In this respect, the level of satisfaction for the programme was very high and we expect that it will be implemented long‐term by our older PWH.